Influence of IQ and mathematical disposition toward the problem solving ability of learners grade VII through PBL learning model with the assistance LKPD - Karsim, Karsim; Suyitno, Hardi; Isnarto, Isnarto (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research is (1) to find out the achievement of ability problem solving learners through learning model PBL with the assistance LKPD; (2) to know the ability problem solving learners through learning model PBL with the assistance LKPD than by the application of learning model PjBL. (3) to find out the influence of IQ toward the ability of problem solving learners through PBL model with the assistance LKPD; (4) to find out disposition mathematical influence on ability toward problem solving learners through PBL model with the assistance LKPD. This research uses quantitative methods and supported by quasi-experimental designs. The subject of this research is students SMPN 41 Semarang grade VII .The data on this research using documentation , the disposition mathematical and tests the ability of solving problems . The end of the results of data , where analyzed by test the average , two test in common an average of , linear regression test and test it simple linear regression double . The research results show that the ability of the solution of a problem learners use the model of learning PBL with the assistance LKPD reached thoroughness and more effective than the application of PjBL kind of classroom . There is a positive influence significantly between IQ and disposition mathematically of the ability of problem solving learners through learning model PBL with the assistance LKPD. Disposition mathematically significantly most influential of the ability of problem solving learners through the application of learning learning model PBL with the assistance LKPD to the matter social arithmetic compared with IQ .